2015
DOI: 10.1007/s13197-015-2030-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seven different drying treatments in respect to total flavonoid, phenolic, vitamin C content, chlorophyll, antioxidant activity and color of green tea (Camellia sinensis or C. assamica) leaves

Abstract: The effect of seven drying treatments (sun, shade, oven 60°C, oven 80°C, oven 100°C, microwave and freezedrying) were evaluated with respect total flavonoid (TFC), phenolic (TPC), antioxidant activity, vitamin C and color characteristics of green tea. In general, drying increased antioxidant activity, TPC, TFC and chlorophyll content, while it led to a decrease in vitamin C. The highest TPC (209.17 mg Gallic acid/gdw) and TFC (38.18 mg Quercitin/gdw) were obtained in oven drying at 60 and 100°C, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
152
6
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(183 citation statements)
references
References 38 publications
16
152
6
9
Order By: Relevance
“…L) was done in comparison with gallic acid equivalent/g [57]. Another research exploration on different drying treatments for green tea also evaluated total phenolic content based on gallic acid equivalent [58]. Further, Rosmarinic Acid, a New Polyphenol from Baccaurea ramiflora Lour.…”
Section: Other Uses Of Gallic Acidmentioning
confidence: 99%
“…L) was done in comparison with gallic acid equivalent/g [57]. Another research exploration on different drying treatments for green tea also evaluated total phenolic content based on gallic acid equivalent [58]. Further, Rosmarinic Acid, a New Polyphenol from Baccaurea ramiflora Lour.…”
Section: Other Uses Of Gallic Acidmentioning
confidence: 99%
“…These results confirm the findings of (Arslan and Ö zcan 2010;Igual et al 2012) who found a better TPC retention in fruits and vegetables using MD compared with OD method; also Chan et al (2009), reported that oven, sun-drying and microwaves, caused significant decrease in the TPC in ginger leaves. Nevertheless, different studies have shown that drying processes may result in lower or higher levels of TPC depending on the type of phenolic compound present in the plant material and their location in the cell (Arslan and Ö zcan 2010;Hamrouni-Sellami et al 2013;Roshanak et al 2016;Verma et al 2015). For instance: sage plants dried in a microwave oven (800 W) showed an increase of 4.2-fold in TPC after drying (Hamrouni-Sellami et al 2013) while Zheng et al (2015) reported a significant decrease in TPC during the drying of loquat flower by using freeze drying, microwave, vacuum and hot-air drying.…”
Section: Effect Of Drying On Phenolic Compound Contents (Tpc)mentioning
confidence: 99%
“…During drying, many phenomena are responsible of color changes. The most common ones are pigment degradation (e.g., chlorophylls and carotenoids) [52] and the occurrence of browning, due both to enzymatic and non-enzymatic reactions [53].…”
Section: Color Changesmentioning
confidence: 99%
“…However, it should be noted that the type of product, origin, pre-treatment and type of drying affect the degradation rate of chlorophylls and carotenoids [54] Furthermore, high temperature and low pH stimulate the conversion of chlorophylls into pheophytins by replacing the central magnesium in the chlorin ring with two hydrogen ions [56]; when chlorophyll is converted into pheophytin, the color changes from light-bright green to olive brown. The conversion rate of pheophytins' formation seems to be slowed down at a water activity (a w ) lower than 0.32 [52]. In addition to this reaction, chlorophyll degradation is related to fat peroxidation.…”
Section: Chlorophylls and Carotenoidsmentioning
confidence: 99%